Teaching and Learning English in a ‘Non-textbook’ Environment (Journal of NELTA, 2021)
This research paper aims at exploring the non-textbook environment in English classrooms. This study has portrayed the limitations of textbooks highlighting the eﬀectiveness in learners’ achievements when teaching English in a non-textbook environment. With an ethnographic inquiry, the study reflects the author’s experience of being in the non-textbook environment through the portrayal of her subjectivity. The methods to collect data were participant/field observation and interview. The exploration of students’ learning while in the non-textbook environment has been depicted in the paper. Overall, the paper anticipated to extend the mindfulness upon the teachers who can think of including activities in an English language classroom without textbooks.